Energy Exchange, Association Agreement with the European Union and Legal Challenges for the Georgian Energy Law - Partsvania, Maka; Gegenava, Dimitry (Review of European and Comparative Law, 2023)
Georgia signed an Association Agreement with the European Union in 2014, and this launched a process of approximation and harmonization with EU law. Energy law is one of the most important areas, which has to be developed and modified in accordance with the EU directives, regulations and rules of the Energy Community. Georgia took responsibility for establishing the energy exchange system and reorganizing the Georgian electricity market on a new model. In fact, these issues have not been studied, as they require, on the one hand, a very in-depth, practical knowledge of the issue and, on the other hand, erudition in the issues of legal approximation and information about the obligations assumed by the association agreement. The purpose of the article is to review the legislative regulations on the Georgian electricity market, the legal framework that defines the main principles of the market, the basis of operation, and sociopolitical and legal mechanisms of market stability. In the article, special attention will be paid to the status of the energy exchange in Georgia, its concept, its legal basis, problematic issues related to its implementation, and the future perspective. As a result of the analysis of the issues, based on the evaluation of the existing problems, the necessary legal ways of the development of energy law and the mechanisms promoting harmonization with the laws of the European Union are determined.